Keluarga Sakinah dalam Perspektif Fiqih Sunnah Sayyid Sabiq - Andi Iswandi; Fathur Rohman (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2022)
The concept of Sakinah according to Sayyid Sabiq is that by marrying which is recommended by Islam, for the sake of his survival, humans do what is within them, namely in the form of fitrah. Sakinah family is the hope of every couple after the wedding, it needs to be prepared since the bridal couple wants to carry out the wedding. Apart from that, in marriage, women are protected from men who lust after her. By forming a marriage there is also the love of a father and mother, therefore both parents teach their children well. Allah SWT blesses marriage like this and is dreamed of by every believer so that he can create a sakinah, mawaddah and warahmah family. Things that must be prepared from a small part in marriage to lead to a sakinah family such as, the bridal couple has mature thoughts for marriage, both physically and mentally, understands the rights and obligations between husband and wife, has sufficient economy, and understands the importance of home the sakinah ladder and the problems that will be passed after the wedding. The ways to choose a life partner are: (1) Have a good environment, (2) A wife who can have children, (3) Get peace when looking at her, (4) Virgins are preferred, and (5) marry someone equal to herself. Promoting harmony in the household, namely: rights and obligations between husband and wife and together.